2016
DOI: 10.1007/s12035-015-9651-y
|View full text |Cite|
|
Sign up to set email alerts
|

Progesterone Changes VEGF and BDNF Expression and Promotes Neurogenesis After Ischemic Stroke

Abstract: Studies have shown that progesterone enhances functional recovery after ischemic stroke, but the underlying mechanisms are not completely understood. Therefore, we investigated the effect of progesterone on vascular endothelial growth factor (VEGF), brain-derived neurotrophic factor (BDNF), and neurogenesis in a rodent stroke model. Rats underwent permanent middle cerebral artery occlusion (pMCAO) and then received intraperitoneal injections of progesterone (15 mg/kg) or vehicle at 1 h followed by subcutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 59 publications
1
32
0
1
Order By: Relevance
“…Based on these previous reports and the limited therapeutic options for ICH, we tested the therapeutic effect of progesterone for ICH in a rodent model. As in the animal models of ischemic stroke and TBI (Barha, et al, 2011, Jiang, et al, 2016), we found that progesterone is neuroprotective in the mouse collagenase-induced ICH model. However, recently completed clinical trials with progesterone failed to demonstrate any neuroprotective effect in patients with TBI (Jickling and Sharp, 2015, Schwamm, 2014).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Based on these previous reports and the limited therapeutic options for ICH, we tested the therapeutic effect of progesterone for ICH in a rodent model. As in the animal models of ischemic stroke and TBI (Barha, et al, 2011, Jiang, et al, 2016), we found that progesterone is neuroprotective in the mouse collagenase-induced ICH model. However, recently completed clinical trials with progesterone failed to demonstrate any neuroprotective effect in patients with TBI (Jickling and Sharp, 2015, Schwamm, 2014).…”
Section: Discussionsupporting
confidence: 56%
“…Progesterone has been shown to have multiple neuroprotective effects. Previous studies also have shown that it has neurotrophic effects and anti-excitotoxic effects (Jiang, et al, 2016, Singh and Su, 2013a). Moreover, progesterone-regulated neural responses may be mediated by membrane progesterone receptors (α-, β-, and γ-isoforms), putative γ-aminobutyric acid type A receptors, or progesterone membrane receptor component 1 (PGRMC1) (Liu, et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Для эстрадиола подобный эффект показан не был [53]. Большое количество современных работ посвящено изучению влияния прогестерона на нервную ткань и функцию центральной нервной системы (ЦНС) [25,27,33]. Доказана способность прогестерона связываться с рецепторами к нему в ЦНС и модулировать поведение и настроение млекопитающих через геномный и неге-номный пути влияния [50].…”
Section: другие биологические эффекты прогестеронаunclassified